FORMAL VERSUS AGILE: SURVIVAL OF THE FITTEST? - Black, Sue; Boca, Paul P.; Bowen, Jonathan P.; Gorman, Jason; Hinchey, Mike (Computer (00189162), 2009)
The article examines the formal and agile approaches to software engineering. The entry notes that formal methods were adopted in software development terms in the 1970s, while agile methodologies began in 2001 with main-value propositions that focused on responding to change, interaction, working software, and customer collaboration. The integration of formal and agile methodologies in software development has been proposed by researchers in their use of the Symbolic Model Verifier (SMV), and in the KeY methodology for object-oriented systems.